Knowledge and Practice of Handwashing by School Students in Kamrup Metropolitan, Assam, India: A Cross Sectional Survey - Sharma, Pawan; Aggarwal, Tanya; Kalita, Manoj; Kumar, Arvind; Mukherjee, Anupam; Chaubey, Daulat Kumar (Homœopathic Links, 2023)
Objective The aim of this study was to understand the level of handwashing knowledge, and handwashing practices as well as to determine the availability of handwashing facilities in the schools.Materials and Methods A survey was conducted on 17th October 2019 to determine the availability of handwashing facilities along with the level of handwashing knowledge and practices among school students of Borsojai High School situated in Kamrup Metropolitan City, Guwahati, Assam. The study population consisted of randomly selected students of 9th and 10th classes during the academic year 2019 to 2020. The quantitative data were analysed using the IBM-SPSS, version 20.0.Result Fifty-six school students from classes 9 to 10th of mean age 15.53 years participated in the current study. It is evident that school-aged students have sufficient knowledge of handwashing, and they widely recognise the importance of handwashing (94.6%) to prevent diseases (39.3%) and to remove germs (48.2%).Conclusion To encourage hand hygiene in school students, parents can also be sensitised through the parents teacher meeting. This will improve the health and reduce the absenteeism from school due to infectious diseases.
Keywords: handwashing; knowledge; practice; school students; disease prevention; Kamrup; Assam